TET-Mediated Epigenetic Regulation in Immune Cell Development and Disease - Tsiouplis, Nikolas James; Bailey, David Wesley; Chiou, Lilly Felicia; Wissink, Fiona Jane; Tsagaratou, Ageliki (Frontiers in Cell and Developmental Biology, 2021)
TET proteins oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) and further oxidation products in DNA. The oxidized methylcytosines (oxi-mCs) facilitate DNA demethylation and are also novel epigenetic marks. TET loss-of-function is strongly associated with cancer; TET2 loss-of-function mutations are frequently observed in hematological malignancies that are resistant to conventional therapies. Importantly, TET proteins govern cell fate decisions during development of various cell types by activating a cell-specific gene expression program. In this review, we seek to provide a conceptual framework of the mechanisms that fine tune TET activity. Then, we specifically focus on the multifaceted roles of TET proteins in regulating gene expression in immune cell development, function, and disease.